Polityka emancypacji kobiet oraz mniejszości seksualnych na przykładzie e-sportu: wprowadzenie do tematyki badawczej = The politics of the emancipation of women and sexual minorities in e-sports: an introduction to the research field - Kołodziej, Marek (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article focuses on the politics of emancipation of women and sexual minorities in e-sports. It discusses emancipation mechanisms, which use virtual sports competition as a tool. Due to the fact that e-sports is a relatively young phenomenon, the topic of egalitarianism and equality measures in e-sports has not yet been the subject of scientific reflection.The problem was investigated using the concept of the politics of emancipation as defined by Anthony Giddens. The research process uses a neo-institutional approach and the results are presented in the form of an analysis. This article conceptualizes the basic concepts of the research field and initiates a scientific discussion on the subject.
Keywords: emancypacja; e-sport; kobiety; mniejszości seksualne; emancipation; e-sports; women; sexual minorities